2020
DOI: 10.1186/s40792-020-01025-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for colloid carcinoma of the pancreas with portal vein tumor thrombus: a case report

Abstract: Background The portal vein is occasionally invaded by advanced malignant tumors in the pancreatic head region. However, pancreatic cancer rarely has portal vein tumor thrombi. We report a case of pancreatic cancer with a massive portal vein tumor thrombus undergoing pancreatoduodenectomy with combined resection of the portal vein. Case presentation A 71-year-old man visited a clinic with complaints of abdominal discomfort and vomiting. Gastroscopy showed a massive tumor in the duodenum. He was referred to ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…It is supposed that the 5-year survival rate for CC following radical surgical resection was 60%; however, the significance of this outcome in CC is uncertain because the study did not examine the influence of postoperative adjuvant therapy. Another case report described gastrointestinal hemorrhage caused by CC, and surgical excision of the tumor may be advantageous ( 39 ). Adsay et al ( 6 ) analyzed 17 CC cases and found that 10 successfully underwent radical surgical resection with an 88% resection rate.…”
Section: Discussionmentioning
confidence: 99%
“…It is supposed that the 5-year survival rate for CC following radical surgical resection was 60%; however, the significance of this outcome in CC is uncertain because the study did not examine the influence of postoperative adjuvant therapy. Another case report described gastrointestinal hemorrhage caused by CC, and surgical excision of the tumor may be advantageous ( 39 ). Adsay et al ( 6 ) analyzed 17 CC cases and found that 10 successfully underwent radical surgical resection with an 88% resection rate.…”
Section: Discussionmentioning
confidence: 99%